PI3K/Akt in platelet integrin signaling and implications in thrombosis. (September 2015) - Guidetti, Gianni F.; Canobbio, Ilaria; Torti, Mauro
Abstract: Blood platelets are anucleated circulating cells that play a critical role in hemostasis and are also implicated in arterial thrombosis, a major cause of death worldwide. The biological function of platelets strongly relies in their reactiveness to a variety of extracellular agonists that regulate their adhesion to extracellular matrix at the site of vascular injury and their ability to form rapidly growing cell aggregates. Among the membrane receptors expressed on the cell surface, integrins are crucial for both platelet activation, adhesion and aggregation. Integrin affinity for specific ligands is regulated by intracellular signaling pathways activated in stimulated platelets, and, once engaged, integrins themselves generate and propagate signals inside the cells to reinforce and consolidate platelet response and thrombus formation. Phosphatidylinositol 3-Kinases (PI3Ks) have emerged as crucial players in platelet activation, and they are directly implicated in the regulation of integrin function. This review will discuss the contribution of PI3Ks in platelet integrin signaling, focusing on the role of specific members of class I PI3Ks and their downstream effector Akt on both integrin inside-out and outside-in signaling. The contribution of the PI3K/Akt pathways stimulated by integrin engagement and platelet activation in thrombus formation and stabilization will also be discussed in order to highlight the possibility to target these enzymes in effective anti-thrombotic therapeutic strategies.